Analisis Wacana Kritis Berita Kasus Korupsi Setya Novanto Di Majalah Online Tempo Edisi November 2017 - Aminudin, Amin (Fakultas Ilmu Komunikasi - Universitas Budi Luhur, 2020)
2017 is a very busy year of political reporting, especially corruption cases, this time the corruption case setya novanto. This case became a news topic discussed by several mass media, not least the coverage of the TEMPO Online magazine published in the November 2017 issue. The purpose of this study was to determine the critical discourse of Setya Novanto's corruption in TEMPO Online Magazine. The method used in this research is qualitative method. The data collection technique was carried out using the documentation technique using Teun Van Dijk's Critical Discourse Analysis theory. The research data is in the form of TEMPO magazine November 2017 edition. The results of this study are reviewed from the macro structure, superstructure, and micro structure used by TEMPO Online magazine reporters in the Setya Novanto corruption news text with the headline